Engineered GM-CSF polarizes protumorigenic tumor-associated macrophages to an antitumorigenic phenotype and potently synergizes with IL-12 immunotherapy - Yue Wang; Kevin Chang; Aslan Mansurov; Jun Ishihara; Seounghun Kang; Trevin Kurtanich; Hye Rin Chun; Anna J Slezak; Lisa R Volpatti; Thomas Wang; Aaron T Alpar; Kirsten C Refvik; et al. (Journal for ImmunoTherapy of Cancer)
Background The use of immune checkpoint inhibitors (CPIs) has become a dominant regimen in modern cancer therapy, however immune resistance induced by tumor-associated macrophages (TAMs) with immune suppressive and evasion properties limits responses. Therefore, the rational design of immune modulators that can control the immune suppressive properties of TAMs and polarize them, as well as dendritic cells (DCs), toward a more proinflammatory phenotype is a principal objective in cancer immunotherapy.Methods Here, using a protein engineering approach to enhance cytokine residence in the tumor microenvironment, we examined combined stimulation of the myeloid compartment via tumor stroma-binding granulocyte–macrophage colony-stimulating factor (GM-CSF) to enhance responses in both DCs and T cells via stroma-binding interleukin-12 (IL-12). We evaluated tumor responses at the levels of outcome, cellular responses, and cytokine responses in both the tumors and the tumor-draining lymph nodes. We further investigated the potentiation of DC response to IL-12 by GM-CSF stimulation ex vivo.Results Engineered GM-CSF restored an antitumorigenic tumor myeloid microenvironment otherwise suppressed by TAMs, while engineered IL-12 provided effector signals to T cells, thereby boosting both tumor-resident antitumor macrophage and CD8+ T cell populations. Furthermore, engineered GM-CSF potentiated DC response to IL-12, upregulating DC expression of IL-12 receptor and enhancing their expression of proinflammatory cytokines and chemokines on IL-12 exposure. This resulted in remarkable synergistic efficacy in multiple solid tumor models treated with the dual cytokine combination. The combination therapy also improved the efficacy of CPI in a CPI-resistant genetically-engineered melanoma model and exhibited synergistic antitumor efficacy in a pulmonary metastasis model.Conclusion Our strategy provides a rational design for combination immunotherapy targeting both myeloid and lymphoid compartments through complementary mechanisms.